Aggregated data from two double-blind base station provocation studies comparing individuals with idiopathic environmental intolerance with attribution to electromagnetic fields and controls. - Eltiti, S; Wallace, D; Russo, R; Fox, E (Wiley, 2015)
Data from two previous studies were aggregated to provide a statistically powerful test of whether exposure to electromagnetic fields (EMFs) produced by telecommunication base stations negatively affects well-being in individuals who report idiopathic environmental illness with attribution to electromagnetic fields (IEI-EMF) and control participants. A total of 102 IEI-EMF and 237 controls participated in open provocation trials and 88 IEI-EMF and 231 controls went on to complete double-blind trials in which they were exposed to EMFs from a base station emitting either a Global System for Mobile Communication and Universal Mobile Telecommunications System or a Terrestrial Trunked Radio Telecommunications System signal. Both experiments included a comparison sham condition. Visual analog and symptom scales measured subjective well-being. Results showed that IEI-EMF participants reported lower levels of well-being during real compared to sham exposure during open provocation, but not during double-blind trials. Additionally, participants reported lower levels of well-being during high compared to low load trials and this did not interact with radiofrequency-EMF exposure. These findings are consistent with a growing body of literature indicating there is no causal relationship between short-term exposure to EMFs and subjective well-being in members of the public whether or not they report perceived sensitivity to EMFs.